PENGARUH EARNING PER SHARE, RETURN ON ASSET, NET PROFIT MARGIN, DAN DIVIDEND PAYOUT RATIO TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2017 - 2023 - Putri, Anastasya Azzahra Maharani; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2024)
Manufacturing is one sector of the Indonesian economy that is quite important and that draws a lot of interest from investors. Before buying or selling shares, investors should keep an eye on the company's performance to minimize potential risks. The purpose of this study is to ascertain how EPS, ROA, NPM, and DPR affect the share price of manufacturing sector businesses that are listed on the IDX between 2017 and 2023. Previous research yielded varying outcomes since it focused on a single manufacturing subsector. The quantitative research approach is panel data regression analysis. The study's conclusions indicate that whereas EPS and ROA have a considerable impact on stock prices, NPM and DPR do not. The combination of EPS, ROA, NPM, and DPR significantly affects stock price. With these results, it is expected that companies can focus on strategies to increase EPS and ROA to increase investor attractiveness and stock prices.